Hepatitis C virus vaccine candidates inducing protective neutralizing antibodies. (1st December 2016) - Fauvelle, Catherine; Colpitts, Che C.; Keck, Zhen-yong; Pierce, Brian G.; Foung, Steven K. H.; Baumert, Thomas F.
ABSTRACT: Introduction : With more than 150 million chronically infected people, hepatitis C virus (HCV) remains a substantial global health burden. Direct-acting antivirals have dramatically improved viral cure. However, limited access to therapy, late stage detection of infection and re-infection following cure illustrate the need for a vaccine for global control of infection. Vaccines with induction of neutralizing antibodies (nAbs) have been shown to protect successfully against infections by multiple viruses and are currently developed for HCV. Areas covered : Here we review the progress towards the development of vaccines aiming to confer protection against chronic HCV infection by inducing broadly nAbs. The understanding or viral immune evasion in infected patients, the development of novel model systems and the recent structural characterization of viral envelope glycoprotein E2 has markedly advanced our understanding of the molecular mechanisms of virus neutralization with the concomitant development of several vaccine candidates. Expert commentary : While HCV vaccine development remains challenged by the high viral diversity and immune evasion, marked progress in HCV research has advanced vaccine design. Several vaccine candidates have shown robust induction of nAbs in animal models and humans. Randomized clinical trials are the next step to assess their clinical efficacy for protection against chronic infection.